The mapmaker and the ghost - Tash, Sarvenaz (Walker & Co., 2012)
The summer before starting middle school, when eleven-year-old Goldenrod Moram sets out to make a very accurate map of the forest behind her home, she discovers a band of troublemakers, a mysterious old lady, and the ghost of her explorer idol.